A Case of Acquired Hemophilia A in a Patient with Exposure to COVID-19 - Guerra, Jorge D.; Gowarty, Jasmine; Buess, Jordan; Mason, James; Halka, Kathleen (Case Reports in Hematology, 2022)
Acquired Hemophilia A (AHA) is a very rare autoimmune condition involving immune-mediated depletion of Factor VIII, resulting in spontaneous hemorrhage. Failure to recognize AHA as a possible etiology of hemorrhage can result in delayed diagnosis and treatment. The COVID-19 pandemic has given rise to several hematologic conditions and complications, with a rare manifestation being Acquired Hemophilia A (AHA). An interesting case of AHA following SARS-CoV-2 infection is described, along with the treatment approach and a brief review of several cases describing AHA in association with COVID-19.